An Edgy Journey through Queer Mobility - Winton, Ailsa (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
Emerging from in-depth research on mobility and displacement in relation to gender and sexual diversity on the Mexico-Guatemala border, this paper reflects on the complexities of lived, queer mobility over space and time as told by Andrea, a 27-year-old Salvadoran trans woman. Her narrative – told to the reader through video – provides a rich account of her affective journeys and the forces behind them, which go beyond movement as migration. The work is part of an improvised mobile, longitudinal ethnography which evolved as a way of exploring the small and large-scale realities of mobility as lived over time. The discussion engages with Andrea’s mobility as non-linear, multi-scalar, spatially and sensorially significant, and emotionally ambiguous. It invites reflection about the powerfully productive and damaging edges of precarious queer mobility, and points to the radical potential of an affective engagement with queer narratives. The queerness of mobility and survival exists not only as an abstract or symbolic edginess, but rather in, and as, constant frictions produced by the struggle for a life worth living.